An Indole Alkaloid Extracted from Evodia rutaecarpa Inhibits Colonic Motility of Rats In Vitro - Guo-xiang Wang; Yan-li Xiang; Hong-gang Wang; Yang-de Miu; Guang Yu (Gastroenterology Research and Practice)
Evodiamine (Evo) is an indole alkaloid extracted from the traditional Chinese medicinal herb Evodia rutaecarpa. Evo may regulate gastrointestinal motility, but the evidence is insufficient, and the mechanisms remain unknown. The aim of this study was to investigate the effect of Evo on colonic motility of rats and the underlying mechanisms in vitro. Rat colonic muscle was exposed to Evo (10 and 100 μM) followed by immunohistochemistry of cholecystokinin receptor 1 (CCK1R). Muscle contractions were studied in an organ bath system to determine whether CCK1R, nitric oxide (NO), and enteric neurons are involved in the relaxant effect of Evo. Whole-cell patch-clamp was used to detect L-type calcium currents (ICa,L) in isolated colonic smooth muscle cells (SMCs). CCK1R was observed in SMCs, intermuscular neurons, and mucosa of rat colon. Evo could inhibit spontaneous muscle contractions; NO synthase, inhibitor L-NAME CCK1R antagonist, could partly block this effect, while the enteric neurons may not play a major role. Evo inhibited the peak ICa,L in colonic SMCs at a membrane potential of 0 mV. The current-voltage (I–V) relationship of L-type calcium channels was modified by Evo, while the peak of the I–V curve remained at 0 mV. Furthermore, Evo inhibited the activation of L-type calcium channels and decreased the peak ICa,L. The relaxant effect of Evo on colonic muscle is associated with the inhibition of L-type calcium channels. The enteric neurons, NO, and CCK1R may be partly related to the inhibitory effect of Evo on colonic motility. This study provides the first evidence that evodiamine can regulate colonic motility in rats by mediating calcium homeostasis in smooth muscle cells. These data form a theoretical basis for the clinical application of evodiamine for treatment of gastrointestinal motility diseases.